Using a multidimensional approach to examine TPACK among teacher candidates. Issue 1 (19th August 2020) - Wen, Huijing; Shinas, Valerie Harlow
Abstract: The Technological Pedagogical and Content Knowledge (TPACK) conceptual framework captures the complex nature of teacher knowledge essential for effective teaching in the digital age. TPACK is difficult to assess, however, particularly among teacher candidates whose pedagogical knowledge is developing. This study aimed to examine multiple ways to assess teacher candidates' TPACK development and its application in response to a technology-focused coursework. Using a mixed-method, multi-assessment design, the study sampled 26 teacher candidates enrolled in a graduate-level course. TPACK survey at two time points and multiple course artifacts including course reflection, lesson delivery reflection and unit plan design were used for analysis. Quantitative survey data pointed to the significant growth in all domains of TPACK except for PK. Qualitative reflection data revealed themes supporting the growth in key TPACK domains. However, unit plan analysis revealed some inconsistency with the self-reported survey results, showing the limitation of TPACK survey. Unit plan data revealed variability and limited application of TPACK knowledge among teacher candidates who reported biggest TPACK growth, suggesting the necessity for providing more opportunities for acquiring TPACK in meaningful application. The study extends earlier research findings about the necessity of using multiple sources of information to assess teacher candidates' TPACK development.